Using High Frequency Transcranial Random Noise Stimulation to Modulate Face Memory Performance in Younger and Older Adults: Lessons Learnt From Mixed Findings - Penton, Tegan; Bate, Sarah; Dalrymple, Kirsten A.; Reed, Thomas; Kelly, Maria; Godovich, Sheina; Tamm, Marin; Duchaine, Bradley; Banissy, Michael J. (Frontiers in Neuroscience, 2018)
High-frequency transcranial random noise stimulation (tRNS) has been shown to improve a range of cognitive and perceptual abilities. Here we sought to examine the effects of a single session of tRNS targeted at the ventrolateral prefrontal cortices (VLPFC) on face memory in younger and older adults. To do so, we conducted three experiments. In Experiment 1, we found that younger adults receiving active tRNS outperformed those receiving sham stimulation (i.e. using a between-participant factor for stimulation condition; Experiment 1). This effect was not observed for object memory (car memory) in younger adults (Experiment 2), indicating that the effect is not a general memory effect. In Experiment 3, we sought to replicate the effects of Experiment 1 using a different design (within-participant factor of stimulation – active or sham tRNS to the same individual) and to extend the study by including older adult participants. In contrast to Experiment 1, we found that active tRNS relative to sham tRNS reduced face memory performance in both younger and older adults. We also found that the degree of decline in performance in the active tRNS relative to sham tRNS condition was predicted by baseline ability, with higher performing participants showing the largest decreases in performance. Overall, the results indicate that tRNS to the VLPFC modulates face memory, but that there may be performance and protocol specific moderators of this effect. We discuss these findings in the context of the broader literature showing the importance of individual variation in the outcome of non-invasive brain stimulation intervention approaches. We conclude that while tRNS may have potential as an intervention approach, generalising from single experiment studies to wide application is risky and caution should be adopted in interpreting findings.